Rethinking the theoretical foundation of economics I: The multilevel paradigm - David Sloan Wilson; Dennis J. Snower (Economics: The Open-Access, Open-Assessment Journal, 2024)
This article is the first of a series that offers a new paradigm for economics, the "multilevel paradigm," using generalized Darwinism as its theoretical framework. Generalized Darwinism refers to all processes that combine the ingredients of variation, selection, and replication - not just genetic evolution - making it relevant to the cultural evolution of economic systems that are embedded in political, social, and environmental systems. We contrast the multilevel paradigm with the neoclassical paradigm and other schools of economic thought. The multilevel paradigm, like the neoclassical paradigm, provides an integrative framework for micro- and macro-economics. It also incorporates the meso level, comprising groups of various sizes, linking micro and macro. Other schools of economic thought are not fully integrative in this sense, constituting instead a form of diffuse pluralism. In the integrative framework of the multilevel paradigm, many important ideas that are currently on the periphery of economics are brought toward the core.
Keywords: 330; multilevel paradigm; economic methodology; generalized Darwinism; diffuse pluralism; integrative framework